Determinan Kemandirian Keuangan Daerah - Andini Marselina; Eva Herianti (Jurnal Akuntansi dan Governance, 2022)
The dependency level of regional governments’ financial on central government is quite high, directing this study to further analyze its determinants. This study employs quantitative method with secondary data from the realization reports of regional expenditure revenues in the form of balance sheets and governmental financial reports. 156 reports during 2016-2018 from 56 regencies and cities on the island of Kalimantan are chosen with purposive sampling. The results show that capital expenditures, regional taxes and general allocation funds simultaneously have significant effect on regional government’s financial independence. Partially, capital expenditures and regional taxes also have significant effect on regional government’s financial independence, while general allocation fund has insignificant effect on regional government’s financial independence.